Ranges of moisture-source temperature estimated from Antarctic ice cores stable isotope records over glacial–interglacial cycles - Uemura R.; Masson Delmotte V.; Jouzel J.; Landais A.; Motoyama H.; STENNI, BARBARA (Climate of the Past, 2012)
A single isotope ratio (δD or δ18O) of water is widely used as an air-temperature proxy in Antarctic ice cores. These isotope ratios, however, do not solely depend on air-temperature but also on the extent of distillation of heavy isotopes out of atmospheric water vapor from an oceanic moisture source to a precipitation site. The temperature changes at the oceanic moisture source (ΔTsource) and at the precipitation site (ΔTsite) can be retrieved by using deuterium-excess (d) data. A new d record from Dome Fuji, Antarctica is produced spanning the past 360,000 years and compared with records from Vostok and EPICA Dome C ice cores. To retrieve ΔTsource and ΔTsite information, different linear regression equations have been proposed using theoretical isotope distillation models. A major source of uncertainty lies in the coefficient of regression, βsite which is related to the sensitivity of d to ΔTsite. We show that different ranges of temperature and selections of isotopic model outputs may increase the value of βsite by a factor of two. To explore the impacts of this coefficient on the reconstructed temperatures, we apply for the first time the exact same methodology to the isotope records from the three Antarctica ice cores. We show that uncertainties in the βsite coefficient strongly affect (i) the glacial-interglacial magnitude of ΔTsource; (ii) the imprint of obliquity in ΔTsource and in the site-source temperature gradient. By contrast, we highlight the robustness of ΔTsite reconstruction using water isotopes records.